Relationship Between Stressful Life Events and Depression Among Adolescents: The Mediating Roles of Subcomponents of Executive Function - Wenli He; Qiong Hu; Jiejie Wang; Yingbo Rao; Chen Cheng; Ping Fang; Qiong Zhang; Yunrong Lu (Behavioral Sciences)
Stressful life events are important risk factors in the development of adolescent depression. Executive function is significant in the stress–depression link. However, it is not clear whether there is a specific effect for subcomponents of executive function (working memory, inhibition, and shifting). Therefore, the present study recruited 213 adolescents (mean age (Mage) = 15.19 years, SD = 1.27, range = 12.00–18.00 years, and 53.00% girls) and measured their perceived stress using the questionnaire of the Adolescent Self-Rating Life Events Checklist, working memory ability by two-back tasks, inhibition ability by Stroop tasks, and shifting ability by Wisconsin Card-Sorting tasks. Results showed that stressful life events positively correlated with adolescents’ depression, while stressful life events negatively linked with working memory and inhibition. Depression was negatively associated with working memory and inhibition. No significant correlation was found between shifting and either stressful life events or depression. Mediation analyses revealed that working memory and inhibition mediated the link between stressful life events and adolescent depression, while shifting did not show a mediating effect. Our findings provide further evidence for the precise effect of executive function in the stress–depression link, implicating that different subcomponents should be considered to provide targeted intervention to alleviate adolescents’ depressive symptoms.